Restorative Justice Settlement of Fraud Crime Case (A Case Study in The North Kuta Badung Police Sector) - Wijaya, I Made Guna; I Made Mulyawan Subawa; Ni Ketut Wiratny (International Journal of Contemporary Sciences (IJCS), 2024)
Restorative justice is an approach in law enforcement that focuses more on recovery and reconciliation between perpetrators, victims, and the community rather than just imposing penalties to repair the social and emotional impact of criminal acts and rebuild damaged relationships. Settlement through restorative justice in its application there is still a conflict of legal norms between the Criminal Code and Perkap Number 8 of 2021 concerning handling criminal acts based on restorative justice in criminal law enforcement in Indonesia, this is because the article to ensnare the perpetrators of fraud is already available and only needs to be implemented, but the reality in the field is that there is still a vital justice approach, even though there have been peace efforts that should have stopped the investigation but the investigators are continuing because settlement through restorative justice cannot necessarily eliminate investigations and or investigations. The problem in this study is the settlement of restorative justice against fraud cases in the North Kuta Sector Police and the obstacles faced in the settlement through restorative justice against fraud cases